Prevalence of varied perception of mothers about their under-five child’s nutritional status with the measured status and the factors associated with the varied perception of mothers. a cross-sectional study in slums of Dhaka city, Bangladesh - Sarker, Tanmoy (Brac University, 2023)
This project report is submitted in partial fulfillment of the requirements for the degree of Master of Public Health (MPH), 2023.